Swedish fraktur 1626-1816 - Språkbanken Text (University of Gothenburg, 2024)
Svensk fraktur 1626 – 1816 contains a selection of digitized versions of older fraktur prints from 1626 to 1816 with their corresponding manual transcriptions. The material was digitized by the Gothenburg University Library, and the digitized versions were manually transcribed by GREPECT using double-keying.

The material was produced as a part of the project A free cloud service for OCR with the aim to improve the OCR interpretation of printed fraktur texts.

The number of digitized pages is 199 and the transcribed texts contain 47924 words in total. The list of titles, libris-ids and publishing links is available here.

Svensk fraktur 1626 – 1816 innehåller ett urval av digitaliserade versioner av äldre frakturtryck från 1626 till 1816 med motsvarande manuell transkribering. Materialet digitaliserades av Göteborgs universitetsbibliotek, och de digitaliserade versionerna transkriberades manuellt av GREPECT genom en s.k. double-keying metod.

Materialet har tagits fram under projektet En fri molntjänst för OCR för att förbättra OCR-tolkningen av tryckta fraktur texter.

Antalet digitaliserade sidor är 199 och de transkriberade texterna innehåller 47924 ord totalt. Listan över titlarna, libris-id:s och publiceringslänkar finns tillgängligt här.
Svensk fraktur 1626-1816
Keywords: Language Technology (Computational Linguistics); fraktur; OCR; reference text; corpus; Natural Language Processing; Språkbehandling och datorlingvistik